HUBUNGAN ANTARA PRAKTEK GIZI SEIMBANG DENGAN KADAR HEMOGLOBIN MAHASISWA PROGRAM STUDI PENDIDIKAN DOKTER ANGKATAN 2013 FK UNSRAT - Ngangi, Fernando R. (Universitas Sam Ratulangi, 2014)
Abstract: Hemoglobin levels are abnormally common in school-age children and college students, students who are not healthy can experience difficulties in the learning process, food intake of these students also depends how the individual wants to consume foods that are nutritious or not. Indonesian Dietary Guidelines using general guidelines balanced nutrition in regulating healthy foods every day, an imbalance between food consumed and the needs of these adolescent will cause problems in the adolescent nutrition. The purpose of this study is to determine the relationship between the practice of dietary guidelines with hemoglobin levels at student year class of 2013 department of general medicine, Faculty of Medicine Sam Ratulangi University. Design of this research using the cross sectional analytic study. Sample was determined by systematic random sampling and made proportional to 2 types of male and female and samples that meet the inclusion criteria, totaling 75 people. Data were collected through questionnaires of practice of dietary guidelines and through the measurement of hemoglobin levels, then the data were analyzed using the Fischer Exact test. Conclusion: The results of the study by Fischer exact test p-value obtained is 0.586 (p>0.05), which means there is no significant relationship between the practice of dietary guidelines with hemoglobin levels. Key words: Dietary Guidelines, Hemoglobin Abstrak: Kadar Hemoglobin yang tidak normal sering dijumpai pada anak usia sekolah dan mahasiswa, mahasiswa yang tidak sehat dapat mengalami kesulitan dalam proses pembelajaran, asupan makanan dari mahasiswa pun tergantung bagaimana individu tersebut ingin mengkonsumsi makanan yang bergizi atau tidak. Indonesia Dietary Guidelines menggunakan pedoman umum gizi seimbang dalam mengatur makanan yang sehat setiap hari, ketidakseimbangan antara makanan yang dikonsumsi dengan kebutuhan pada remaja akan menimbulkan masalah gizi pada remaja tersebut Penelitian ini bertujuan untuk mengetahui hubungan antara praktek gizi seimbang dengan kadar hemoglobin mahasiswa program studi pendidikan dokter angkatan 2013 Fakultas Kedokteran Universitas Sam Ratulangi. Rancangan penelitian ini bersifat analitik dengan menggunakan pendekatan potong lintang (cross sectional). Sampel penelitian ditentukan secara systematic random sampling dan dilakukan proposional untuk 2 jenis kelamin laki-laki dan perempuan dan sampel yang memenuhi kriteria inklusi berjumlah 75 orang. Data yang dikumpulkan melalui kuisioner praktek gizi seimbang dan melalui pengukuran kadar hemoglobin, kemudian data dianalisis dengan menggunakan uji Fischer Exact. Kesimpulan :Hasil penelitian dengan uji Fischer Exact diperoleh nilai p yaitu 0,586 (p>0,05), yang artinya tidak ada hubungan yang signifikan antara praktek gizi seimbang dengan kadar hemoglobin Kata Kunci: Praktek Gizi Seimbang, Hemoglobin